IS WOMEN POLITICAL INCLUSION AN END IN ITSELF IN RWANDA? A META-SYNTHESIS OF QUALITATIVE AND QUANTITATIVE EVIDENCES - Mumporeze, Nadine; Nduhura, Dominique (PEOPLE: International Journal of Social Sciences, 2019)
Informed by the theory of women’s political representation, the present paper employs a thematic meta-synthesis method to investigate whether or not women political inclusion in political institutions furthers gender equality in Rwandan society. The main findings suggest that Rwanda has achieved high political representation of women, which may increase power for some women by allowing them to have a greater voice in society and access to education. However, numerous women do not ensure gender equality in all spheres of life as they continue to suffer excessively from politico-ethnic exclusion, unemployment, poverty, heavy domestic responsibilities, gender-based violence, and lack of access to health care services. Legal changes and policies designed to promote gender equality are unquestionably worsening. Although an underlying economic rationale remains leading, gender policies and strategies are implemented with attention to quantitative results rather than qualitative outcomes. Our findings suggest that the current statistics on the gender gap do not express the real situation of Rwandan women. Besides, these findings yield a theory that high women's political participation may not translate into gender equality. Future research should aim to explore possible solutions to the identified problems.